Newborns : how baby animals come into the world - Jara Straussmann, Paulina; Galí, Mercè; Schimel, Lawrence (Orca Book Publishers, 2025)
"In this nonfiction picture book, learn about a diverse group of animal parents and babies, from alpine salamanders to polar bears, scorpions to walruses, in simple, kid-friendly language paired with vibrant illustrations."--